Molecular assessment of native fish diversity in UNESCO heritage site, Tasik Raban, Malaysia using DNA barcoding: DNA Barcoding of Native Fishes in Tasik Raban, Malaysia - Ramizah Abdull Rahman; Adibah Abu Bakar; Nurul Fizatul Nabilah Osman; Syazwan Saidin; Intan Faraha A. Ghani (Genetikawan Muda Indonesia, 2021)
Despite the fact that freshwater fishes have been studied for over a century, Malaysia's conservation status and management are still in their infancy. The poor progress of freshwater fish taxonomy and conservatory management is primarily due to a lack of interest and funding. There are still numerous unsolved taxonomic issues of freshwater fishes in Malaysia and this had a negative impact on national ichthyological research. As a result, the current research aims to aid the success of the molecular DNA barcode project, particularly in inland reservoirs such as Tasik Raban, Perak which is located in the UNESCO Heritage Site. The Cytochrome c oxidase subunit 1 (COI) marker was used in this project to ensure that native fishes were taxonomically and molecularly barcoded and ready to be accessible through internet databases. Such public references can aid in raising awareness about the management of local fish variety. Taxonomy and molecular characterization data can be utilized to plan future conservation efforts, particularly for depleted, unknown, or cryptic native species.